Análise Estrutural e Comportamental de Aplicações Ginga-NCL Orientada a Conformidade - Prota, Thiago M.; Véras, Douglas; Ferraz, Carlos A. G. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2014: Anais Estendidos do XX Simpósio Brasileiro de Sistemas Multimídia e Web, 2014)
This work aims to present a thesis proposal in the context of Ginga-NCL, proposes a solution that allows analyze the interactive TV applications in this context from two perspectives: structural and behavioral. Thus, seeks to present the theoretical context, emphasizing the problem identification and the proposed objectives. Moreover, presents research planning and development, detailing the current stage of work, the proposed solution and a proposed evaluation. Finally, details the state of the art, assessing the related works.